All Days 2012
DOI: 10.2118/157033-ms
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Mobility of Functionalized Silica Nanoparticles for Enhanced Oil Recovery Applications

Abstract: For any possible application of hard nanoparticles as an improved oil recovery agent, it is necessary to have a stable wettability modifier with improved mobility properties under broader oil reservoir conditions. Typical oil reservoir conditions with high temperature, pH and electrolytes concentration modifies the way that nanoparticles interact with the solution. In this work, the wettability and fluid diffusivity at the molecular level were studied through Molecular Dynamics simulation. We have studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 27 publications
0
82
0
Order By: Relevance
“…In the past decade, most investigations have shown that nanoparticles (NPs) offer promise for future EOR processes where silica-based NPs have been most commonly used [9][10][11][12][13]. Although the oil displacement mechanism via NPs is not yet clearly understood [14][15][16], the nanotechnology is now chosen as an alternative method to unlock the remaining oil resources and applied as a new EOR method in last decade [10][11][12][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, most investigations have shown that nanoparticles (NPs) offer promise for future EOR processes where silica-based NPs have been most commonly used [9][10][11][12][13]. Although the oil displacement mechanism via NPs is not yet clearly understood [14][15][16], the nanotechnology is now chosen as an alternative method to unlock the remaining oil resources and applied as a new EOR method in last decade [10][11][12][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the oil displacement mechanism via NPs is not yet clearly understood [14][15][16], the nanotechnology is now chosen as an alternative method to unlock the remaining oil resources and applied as a new EOR method in last decade [10][11][12][17][18][19][20]. polymeric microspheres and nanospheres have been applied as water mobility control both as a pilot and full-field, and showed fantastic results in reducing water cut, increasing sweep efficiency and improving oil recovery [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, most investigations have shown that nanoparticles (NPs) offer promise for future enhanced oil recovery (EOR) processes where silica-based NPs have been most commonly used [9][10][11][12][13]. Although the oil displacement mechanism with NPs is not yet clearly understood [14][15][16], the nanotechnology is now chosen as an alternative method to unlock the remaining oil resources and applied as a new enhanced oil recovery (EOR) method in the last decade [10][11][12][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although the oil displacement mechanism with NPs is not yet clearly understood [14][15][16], the nanotechnology is now chosen as an alternative method to unlock the remaining oil resources and applied as a new enhanced oil recovery (EOR) method in the last decade [10][11][12][17][18][19][20]. Polymeric microspheres and nanospheres have been applied as water mobility control both as a pilot and full field and showed fantastic results in reducing water cut, increasing sweep efficiency and improving oil recovery [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The nanotechnology is now chosen as an alternative method to unlock the remaining oil resources and applied as a new enhanced oil recovery (EOR) method in last decade (Ju et al 2006;Ogolo et al 2012;Miranda et al 2012;Roustaei et al 2012;Hendraningrat et al 2013a;Hendraningrat and Torsaeter 2014a, b). Das et al (2008) defined ''Nano'' as one billionth (10 -9 ) in science term and nanofluids as suspensions of nanoparticles in base fluids (include saline water, oil, bio-fluids, polymer solutions, etc.).…”
Section: Introductionmentioning
confidence: 99%